Análise de um Programa de Habilidades Sociais para universitários com Transtorno do Espectro do Autismo - Martin, Marina (2024)
The growing increase in the number of individuals diagnosed with Autism Spectrum Disorders reaching adulthood and entering Higher Education raises the issue of the challenges faced in this age group and in this environment. Among them, one that deserves to be highlighted is the importance of a good repertoire of Social Skills for a good university experience. Considering this scenario, this research aims to analyze the PEERS® for Young Adults program, the Social Skills intervention program for young adults with Autism Spectrum Disorders created by the University of California at Los Angeles - UCLA, making considerations about its application and adaptation to the context of public Higher Education Institutions in Brazil. To this end, qualitative exploratory research was conducted, using documentary analysis with data processing in two phases: the first of Content Analysis, in which analysis categories were created by reading the program manual, and the second of Comparative Analysis, in which the already mentioned Brazilian context and its American equivalent, in which the program is already successfully applied, were compared in the categories created during the first phase. These categories were: structure and content of the program, participant profile, tutor profile, and place of application, with more specific subtopics with which the realities of both countries could be contrasted, seeking to understand the feasibility of application in Brazil. We, therefore, consider that public Higher Education Institutions are a possible application space, however, some adaptations are necessary to take into account the specificities of the Brazilian reality. We hope this work can contribute to ensuring that this intervention program is used in Brazil and that future research is conducted on this theme.